The prophetic witness of the church as an appropriate mode of public discourse in African societies - Nyiawung, Mbengu D. (HTS teologiese studies, 2010)
A discussion on the prophetic witness of the church is relevant in many respects. Firstly, most African countries have embraced democracy, without defining its contents; hence, democracy practised in Africa varies from one country to another. Secondly, democracy, itself, has left unpredictable consequences in African societies, where its leaders have cherished what they gain from leadership, rather than thinking in terms of community development. Thirdly, many people have lost confidence in the church in times of misery. The need for a solution to social crisis has created room for alternative modes of public discourse that compete with the church’s prophetic voice of: ‘Thus says the Lord’. Fourthly, churches seem to have established a dichotomy between theology and societal realities. Fifthly, the church has, so far, concentrated most of its efforts on evangelising to the regular faithful who attend the Sunday service and other meetings and have rather neglected those on the streets. Lastly, ‘armchair sermons’, coupled with the effect of democracy seem to have moulded passive and expectant citizens, rather than challenge them to strive for a committed and responsible stewardship. These reasons, and others, account for the situation of misery and underdevelopment of African societies; hence, the need for the development of a ‘relevant theology’ that marches with African realities.